Altered choroid plexus gene expression in major depressive disorder - Turner, Cortney A.; Thompson, Robert C.; Bunney, William E.; Schatzberg, Alan F.; Barchas, Jack D.; Myers, Richard M.; Akil, Huda; Watson, Stanley J. (Frontiers in Human Neuroscience, 2014)
Given the emergent interest in biomarkers for mood disorders, we assessed gene expression in the choroid plexus, the region that produces cerebrospinal fluid (CSF), in individuals with major depressive disorder (MDD). Genes that are expressed in the choroid plexus (CP) can be secreted into the CSF and may be potential biomarker candidates. Given that we have previously shown that fibroblast growth factor family members are differentially expressed in post-mortem brain of subjects with MDD and the CP is a known source of growth factors in the brain, we posed the question whether growth factor dysregulation would be found in the CP of subjects with MDD. We performed laser capture microscopy of the choroid plexus at the level of the hippocampus in subjects with MDD and psychiatrically normal controls. We then extracted, amplified, labeled and hybridized the cRNA to Illumina BeadChips to assess gene expression. In controls, the most highly abundant known transcript was transthyretin. Moreover, half of the 14 most highly expressed transcripts in controls encode ribosomal proteins. Using BeadStudio software, we identified 169 transcripts differentially expressed (p< 0.05) between control and MDD samples. Using pathway analysis we noted that the top network altered in subjects with MDD included multiple members of the transforming growth factor-beta (TGFβ) pathway. Quantitative real-time PCR (qRT-PCR) confirmed downregulation of several transcripts that interact with the extracellular matrix in subjects with MDD. These results suggest that there may be an altered cytoskeleton in the choroid plexus in MDD subjects that may lead to a disrupted blood-CSF-brain barrier.